Correction to “The national curriculum implementation into the operational curriculum based on multiple intelligences theory (Research dissemination before pandemic Covid-19)” - Gandasari, Adriana; Wahyudin, Dinn; Abdulhak, Ishak; Djohar, As’ari (Universitas Airlangga, 2024)
This is a correction to the article “The national curriculum implementation into the operational curriculum based on multiple intelligences theory (Research dissemination before pandemic Covid-19).” The original article has been published in the Indonesian Journal of Social Sciences volume 14, issue 1, January-June 2022, pages 14-25.